Reconstruction algorithm for block compressed sensing based on variation model - Jian CHEN; xiong SUKai; zhi YANGXiu; kui ZHENGMing; qun LINLi (Tongxin xuebao)
The algorithms for block compressed sensing based on total variation and mixed variation (abbreviated as BCS-TV and BCS-MV) models were proposed to improve the performance of current reconstruction algorithms for the block-based compressed sensing. In the measuring phase, an image was sampled block-by-block. In the recovering period, it took the sparse regularization of the natural image as a priori knowledge, and approached the target function within the whole image through the modified augmented Lagrange method and alternating direction method of multipliers (ALM-ADMM). The method proposed achieves average PSNR gain of 1.5 dB and SSIM gain of 0.05 at a more stable running speed, over the previous uniformly block-based compressed sensing. It is particularly suitable for the applications of the multimedia data processing with fixed transmission delay.